2015
DOI: 10.1590/s1519-99402015000100015
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de cálcio na manutenção da qualidade interna de ovos de codornas japonesas após armazenamento

Abstract: <p>O objetivo com este estudo foi avaliar a influência de níveis crescentes de cálcio na dieta na melhoria da qualidade externa e consequente manutenção da qualidade interna de ovos de codornas em final de produção, armazenados por 14 dias em temperatura ambiente. Foram utilizadas 400 codornas japonesas com 46 a 58 semanas de idade, distribuídas em um delineamento inteiramente casualizado onde foram testados cinco níveis de cálcio: 2,95%, 3,25%, 3,55%, 3,85%, 4,15% Ca. Os parâmetros avaliados foram: espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
2
1
Order By: Relevance
“…It is an inevitable phenomenon aggravated by several factors such as the nutritional and sanitary status of the laying hen, egg storage time, and temperature and relative humidity during storage (HENRIQUES et al, 2018). Souza et al (2015) concluded in their study that the inclusion of increasing levels of calcium in the feed is efficient to maintain the internal quality of Japanese quail eggs after storage at room temperature for 14 days, which was not verified in the present study. Based on the results, the increase in shell thickness and weight with increasing inclusion of algae calcareae was not enough to improve the conservation of the internal quality of Japanese quail eggs.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…It is an inevitable phenomenon aggravated by several factors such as the nutritional and sanitary status of the laying hen, egg storage time, and temperature and relative humidity during storage (HENRIQUES et al, 2018). Souza et al (2015) concluded in their study that the inclusion of increasing levels of calcium in the feed is efficient to maintain the internal quality of Japanese quail eggs after storage at room temperature for 14 days, which was not verified in the present study. Based on the results, the increase in shell thickness and weight with increasing inclusion of algae calcareae was not enough to improve the conservation of the internal quality of Japanese quail eggs.…”
Section: Resultscontrasting
confidence: 77%
“…They are a source of calcium and magnesium that acts as a substitute for calcite limestone (MELO et al, 2009). As Souza et al (2015) reported, calcite mineral supplementation improves eggshell thickness and consequently breakage resistance, suggesting that eggs may have a longer shelf life. The aim of this study is thus to evaluate the influence of including levels of calcareous seaweed flour in replacement for calcite limestone on the diet under egg conservation at different storage periods.…”
Section: Introductionmentioning
confidence: 96%
“…According to Mello (2015) , approximately 30% of the calcium present in the egg shells comes from the bones, and this is owing to the fact that in the uterus, where the deposition of calcium carbonate in the egg occurs, there is no storage of calcium. Souza et al. (2015) , while using 5 levels of Ca (2.95, 3.25, 3.55, 3.85, and 4.15%) and a 14-day storage period, obtained better internal quality indexes as the levels of Ca increased.…”
Section: Discussionmentioning
confidence: 93%